Impact of antibiotic treatment for chronic endometritis on pregnancy outcomes in women with reproductive failures (RIF and RPL): A systematic review and meta-analysis - Liu, Jingjing; Liu, Zheng Ai; Liu, Yichun; Cheng, Lei; Yan, Lei (Frontiers in Medicine, 2022)
Objective: To investigate the effect of antibiotic treatment for chronic endometritis (CE) on reproductive outcomes. Design: Systematic review and meta-analysis. Setting: Not applicable. Patient(s): women with reproductive failures including recurrent implantation failure (RIF), and recurrent pregnancy loss (RPL). Intervention(s): Literature searches were performed using three electronic databases (PubMed, Embase, Web of Science) until December 1, 2021(without date restriction). The following comparators were included: women with CE receiving antibiotics vs. untreated controls; women with cured CE vs. women with normal endometrial histology (negative for CE); and women with cured CE vs. women with persistent CE (PCE). The summary measures were indicated as odds ratio (OR) with 95% confidence interval (CI). Main Outcome Measure(s): Ongoing pregnancy rate/live birth rate (OPR/LBR), Clinical pregnancy rate (CPR), Miscarriage rate/Pregnancy loss rate (MR/PLR) Result(s): A total of 2154 women (from twelve studies) were enrolled. Compared with the control group, women with CE receiving antibiotics did not show a statistically significant difference in OPR/LBR (P=.09) and CPR (P=.36), although there was a lower MR(P=.03). Women with cured CE have higher OPR/LBR (OR 1.57) and CPR (OR 1.56) in comparison with those with non-CE. There was a statistically significantly higher OPR/LBR (OR 6.82, P<.00001) and CPR (OR 9.75, P<.00001) in women with cured CE vs. those with persistent CE. Conclusion(s): While antibiotic treatment is a sensible option to cure CE, more well-designed prospective studies are needed to evaluate the reproductive impact of antibiotic treatment.Cured CE provides high-quality maternal conditions for subsequent embryo transfer and successful pregnancy.